Mercado brasileiro de medicamentos genéricos: análise do desemprenho de uma subsidiária de laboratório estrangeiro - Pinto, Celina Maria Duarte Pereira (2007)
The pharmaceutical industry is a segment that is dominated by transnational companies. This characteristic is visible in Brazil, where there are only three domestic laboratories in the top ten pharmaceutical companies list. From the 1970s onwards, the world pharmaceutical market went through deep changes caused mainly to the increase of regulatory control and patent expiration that led to the advent of generic medicaments. In 1999, it was published the law that allowed the introduction of generic medicaments in Brazil, creating a new market that is currently dominated by domestic laboratories. This dissertation proposes to identify the reasons for a subsidiary of foreign laboratory does not achieve the leadership of this market. The literature is based on international political economy and international business concepts that means, relations between subsidiary and head office, domestic and foreign companies and government. Four propositions are presented and tested through multiple sources of evidences. The empirical research was mainly grounded in interviews with key persons and participant observation that allowed access to information, which would be not available for scientific investigation. The results indicate that the relationships considered in this study affect the subsidiary performance in generic medicament market in regard to its ability to make decisions, price competitiveness and wide portfolio creation. The respondents considered those three aspects as success critical factors. The results can be used for future research, aiming to wide the focus of the study about domestic laboratory dominance in generic medicament markets. Another suggestion is to follow this market evolution regarding to the internationalization process of domestic laboratories.